Answer:
[tex]\displaystyle w=\frac{A-Lh}{2l+3H}[/tex]
Explanation:
Solving Equations by Isolation
We have this equation:
[tex]2A= 4lw+2Lh+6wH[/tex]
Let's solve it for w step by step. First, we flip both sides
[tex]4lw+2Lh+6wH =2A[/tex]
Subtracting 2Lh in both sides
[tex]4lw+2Lh+6wH-2Lh =2A-2Lh[/tex]
Simplifying
[tex]4lw+6wH =2A-2Lh[/tex]
Factoring w
[tex]w(4l+6H) =2A-2Lh[/tex]
Dividing by (4l+6H)
[tex]\displaystyle w=\frac{2A-2Lh}{4l+6H}[/tex]
Simplifying by 2:
[tex]\displaystyle \boxed{w=\frac{A-Lh}{2l+3H}}[/tex]